EFFECT OF HIGH CURRENT DENSITY ON THE MORPHOLOGY OF NI/TIN/ALN COMPOSITE LAYERS USING PULSE ELECTRODEPOSITION METHOD: PENGARUH RAPAT ARUS TINGGI PADA MORFOLOGI LAPISAN KOMPOSIT NI/TIN/ALN DENGAN METODE ELEKTRODEPOSISI ARUS PULSA - Dhea Laila Putri Afifah; Esmar Budi; Teguh Budi Prayitno (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
Pulse current for electrodeposition has the advantage of forming smaller grain sizes, porosity and homogeneity, thus having an impact on improving material properties. In this research, the composition of the electrolyte solution that will be used are NiCl2.6H2O 0.17 M, NiSO4.6H2O 0.38 M, TiN 6 gr/L, AlN 10gr/L, H3BO3 0.49 M, and Sodium Dodecyl Sulfate (SDS) 0.6 gr/L. Platinum (Pt) will be used on the counter electrode and Tungsten Carbide (WC) will be used on the working electrode. Variations in pulse current density that will be used are 1 mA/mm2 and 1.2 mA/mm2. The electrodeposition process will be carried out for 30 minutes at 40°C temperature and stirring rate 600 rpm. After the electrodeposition process, morphological characterization was examinated using a Scanning Electron Microscope (SEM). SEM results at 1000x magnification show that at variations in pulse current density of 1 mA/mm2 the particle size is larger, the distribution of particles is quite even, there are neither cracks nor visible agglomeration on the substrate surface, whereas at a current density of 1.2 mA/mm2 ,the particles look smaller, the particles are evenly distributed, there are neither visible cracks nor agglomerations on the substrate surface, so the surface looks smoother. The results show that as the current density increases, the layer surface morphology will become smoother.